Social innovation dynamics: a territorial approach to 3rd sector initiatives in the north of Portugal - Diogo, Vera (2010)
This ongoing project addresses the recent transformations within social policy and practice that gave form to the concept of social innovation. Social innovation is understood as a significant change in the way a given society deals with a social problem. Its significance is measured by scale - number of people, geographical area involved, by scope - its capacity to affect multiple social dimensions, and by resonance - that is, the degree of intensity to which it attracts people's imagination (Nilsson, 2003). The question is to know in which ways is the spatial development and spatial justice (Soja, 2010) affected by the social innovation initiatives carried on within the third sector. The literature on social innovation refers to two main methodologies: working with and not for the people - the conviction that social actors' involvement on the projects that are designed for their benefit is a functional requirement; network cooperation - the understanding that organizations must come out of their walls in order to fully engage with society, for that is the only way to provide an integrated answer to social needs in a network society.The research will approach 3 case studies: a national project on gender equality run by a Local Development Association's network - Animar; a Private Social Institution focused on Health and Wellbeing - Espaço T; and, a Non Profit Association focused on Housing - Associação Humanitária Habitat. This third case is a methodology of housing support based on volunteer work and territorial network activation, therefore of particular interest for this conference.